A Study of Geographical Indications - Kumar Mohapatra, Chinmaya (International Journal of Psychosocial Rehabilitation, 2025)
This paper elucidates the concept of Geographical Indication and the reason of the grant of such protection. As GI comes within the ambit of Intellectual Property, it has broadly been laid down in the various international treaties which have formed the basis for the domestic laws in the member countries. These treaties have been discussed in the paper. The protection granted in India and the remedies available to GI owners have also been talked about before two of the important cases pertaining to GIs in India have been discussed. The paper concludes with laying down the importance of the protection of GIs.